A case of non‐rhododendrol whitening cosmetifucs‐induced leukoderma. Issue 4 (18th June 2019) - Takeo, Naoko; Fujiwara, Sakuhei; Hatano, Yutaka; Kai, Yoshitaka
Abstract : After the use of non‐rhododendrol whitening cosmetics, the patient developed leukoderma in the areas where she applied them. We show the clinical manifestation before (A) and 3 years after (B) treatment with 0.1% tacrolimus ointment.